Pentingnya Peran Pemberdayaan Psikologis Karyawan Bagi Organisasi: a Systematic Literature Review - Josafat Gracia Ginting (PT Maju Malaqbi Makkarana, 2026)
Employees are constantly facing increasingly complex work demands in innovation and demands for high productivity. Psychological empowerment (PE) is a crucial aspect for employees in their work. Psychological empowerment is a condition in which an individual employee feels that their work has meaning, they feel they have good skills and competencies, have the freedom to make decisions and are able to influence the results of the tasks they perform. The purpose of this study is to analyze the role of employee psychological empowerment in influencing the organization as a whole. The method in this study is a Systematic Literature Review (SLR). Data were collected from the Google Scholar database using Publish or Perish 8 software. A total of 35 articles were selected for in-depth analysis using Preferred Reporting Items for Systematic Reviews and Meta Analyses (PRISMA). The results of this study indicate that; (1) psychological empowerment increases employee job satisfaction, active participation, and affective commitment to the organization; (2) psychological empowerment plays a role in strengthening the relationship between leadership style, organizational support, digital competence and emotional intelligence with innovation, creativity and employee performance in the organization; (3) psychological empowerment has a positive effect on employee emotional well-being and mental health; (4) Organizations that adopt strategies, policies and programs that support employee psychological empowerment will be able to increase employee innovation, performance and loyalty.